The Use of Dexamethasone in Bacterial Meningitis in Children and Adults: A Retrospective Analysis. (28th December 2011) - Cornelis, An-Sophie; Hachimi-Idrissi, Said
Abstract : Bacterial meningitis is a life-threatening illness that results from bacterial infection of the meninges and is associated with high mortality and morbidity rate, especially when the Streptococcus pneumoniae is the causative agent. Dexamethasone as adjunctive therapy to antibiotics does not influence the outcome or the complications in children as well as in adults suffering bacterial meningitis. However, we identified some prognostic parameters in the outcome of bacterial meningitis, and when dexamethasone was given in presence of at least one of 3 poor prognostic CSF parameters (WBC < 1000/mm 3, glucose < 20 mg/dl, lactate > 10 mg/dl) it substantially improved the outcome.